EFEKTIVITAS PELAKSANAAN PROGRAM DESA BINAAN DI DESA PUNGGUR BESAR KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Setia Sabta Aditama Putra E.42009039 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
The Implementation of Desa Binaan program At Punggur Besar Village Sungai Kakap District there are various problems that occur. This resulted in the implementation of the public participation Desa Binaan program activities will be reduced, it can be seen from the enthusiasm of the villagers due to the low level of education and public awareness of the program. Another problem is a mismatch programs to local needs, this will also reduce the motivation of the community in the implementation of the program Desa Binaan activities. In this study will be seen how effective the program implementing Desa Binaan activities in the Punggur Besar village. Indicator of the effectiveness of the implementation of Desa Binaan program that is targeting the achievement of goals and targets span concrete, and the integration of that which is the process of Desa Binaan socialization, and adaptation program is the ability of resource actors in adapting to the needs of the target implementation. Data collection is done by interviews, documentation and observation to support the acquisition of data. Based on the results of the analysis of the data suggested that the implementation of Desa Binaan program in the Punggur Besar village largely been implemented, while for socialization programs are implemented with direct meetings with the public and dissemination of information about the program through the media information. In the resource indicator actors of Desa Binaan program in which offenders program implementation required more working hard, perseverance and tireless in the success of this program. Community participation in the implementation of Desa Binaan Program at Punggur Besar village is known that people were active in maintaining, keeping, caring for, from what has been done or carried out either directly or indirectly. Keywords: Effectiveness, Desa Binaan Program, Punggur Besar Village.